Analisis Performance Mesin Weaving Pada Pt Abc Menggunakan Metode Reliability Availability Maintainability (ram) Dan Overall Equipment Effectiveness (oee) - Agung Firman Yusra; Endang Budiasih; Aji Pamoso (eProceedings of Engineering, 2018)
Abstrak PT ABC merupakan perusahaan industri tekstil Indonesia di kabupaten Bandung yang memproduksi sarung menggunakan mesin weaving. Mesin weaving adalah mesin tenun yang otomatisasi, harus memliki performansi bagus dan bekerja optimal. Maka kebijakan maintenance pada mesin weaving harus tepat. Metode yang digunakan Reliability Availability Maintainability (RAM) Analysis pada sistem kritis mesin dan mengetahui nilai performance indicator di sistem kritis mesin weaving. Metode selanjutnya yaitu Overall Equipment Effectiveness (OEE) Analysis untuk mengetahui kinerja dan tingkat efektivitas mesin. Dalam OEE dilakukan perhitungan untuk mengetahui nilai availability, performance rate, dan rate of quality product dari sebuah mesin, serta faktor six big losses untuk mengetahui faktor apa yang menyebabkan nilai OEE rendah. Pada mesin weaving terdapat 4 sub sistem kritis yaitu gun, lade, teropong, dan sisir tenun. Masingmasing sub sistem memiliki R(t) = 16 jam yaitu, gun 94%, lade 95%, teropong 94% dan sisir tenun 96%, sedangkan dengan maintainability selama M(t) = 1 jam sudah bisa mengembalikan keandalannya sebanyak, gun 32%, lade 15%, teropong 57%, dan sisir tenun 17%. Nilai inherent availability system 95% dan operational availability system 78%. Nilai overall equipment effectiveness mesin weaving yaitu, availability 85,28%, performance rate 65,04%, dan quality rate 75,58%. Sehingga nilai OEE 42,11%, sedangkan nilai six big losses terbesar defect losses 36,65%. Kata Kunci –Reliability- Maintenance-Availability, Overall-Equipment-Effectiveness, Six-big-losses. Abstract PT ABC Company is textile industry Indonesia at Bandung District which produces sarong use a weaving machine. Machine weaving loom that is automation, should possess a good performance and optimal work. Then maintenance on the machine weaving must be precise. Methods used Reliability Availability Maintainability (RAM) Analysis on system of critical machinery and know value of the performance indicator on the system critical machine weaving. The next method that is Overall Equipment Effectiveness (OEE) Analysis to know the performance and effectiveness of the machines. In the OEE calculation performed to find out the value of availability, performance rate, rate of quality product from a machine and also to know a factor six big losses make OEE value low. Weaving machine there are 4 sub critical system. gun, lade, teropong, and sisir tenun, when has a R (t) = 16 hours, 94% gun, 95% lade, 94% teropong, and 96% sisir tenun. With maintainability for t = 1 hour can already restore possibly as much as 32% gun, 15% lade, 57% teropong, and 17% sisir tenun. Inherent availability system value 95% and operational availability system value 78%. The value of the overall equipment effectiveness weaving machines, 85.28% availability, 65.04% performance rate, and 75.58% quality rate. So the value of OEE 42.11%, the value of the six big losses the biggest is defects 36.65% losses. Keywords–Reliability-Maintenance-Availability, Overall-Equipment-Effectiveness, Six-big-losses